Business Process Analysis of Academic System Using Business Process Modeling Notation at STMIK STIKOM Indonesia - Dewa Made Adi Baskara Joni; Brigida Arie Minartiningtyas (JEECS (Journal of Electrical Engineering and Computer Sciences), 2016)
STMIK STIKOM Indonesia has implemented the standards set by the government in the management of higher education, one of which is the international standard ISO-9001. In these standards, procedures contained in the management of higher education, limited access to and understanding of the content of university management procedures as well as the form of text-based procedure was judged to be the cause of incomprehension stakeholders resulting in the ineffectiveness of the established procedure. One attempt to solve this problem is to construct a form of media that can be accessed and understood by stakeholders. The media can be a graphical representation in the form of a diagram that can tell the content of the procedure. Based on the results of the analysis showed that the procedure has not been carried out properly so it needs to be improved overall business processes. Modeling using BPMN be the perfect solution to represent a business process flow.